Intracranial Tumor Presenting as Raymond Syndrome in a Pediatric Patient - Tomas-Esteban, Danica; Dizon, April; Ang, Lourdes; Reyes, Karen (Journal of Ophthalmic Science, 2021)
This is a case of a pediatric patient who presented with a sudden onset of right abducens nerve palsy with contralateral hemiplegia with no facial paralysis. With the constellation of symptoms aided by the presence of enhancing pontine mass on magnetic resonance imaging, the presence of diffuse intrinsic pontine glioma (DIPG) was presumed to have caused the findings consistent with the common type of Raymond syndrome.
Keywords: Raymond syndrome; abducens nerve palsy; pontine glioma